100 Years On, How Many More To Go? Challenges Facing Women in Law in 2013 - van Alphen Fyfe, Monique (Victoria University of Wellington Law Review, 2016)
One hundred years on from Harriette Vine’s graduation, women in law are still confronted with discrimination in their careers. This article examines perceptions of women in law and women’s pessimism regarding their prospects. It suggests that legislative, institutional and individual efforts could generate equality within the legal community. Solidarity and agitation to encourage the participation of women at all levels of the profession can best honour the legacy of women’s rights in New Zealand.